(untitled) (Nigerian Journal of Technology, 2016)
Water scarcity is one of the major problems facing some cities of the world and wastage during transmission has been identified as a major problem. In this paper a Microcontroller Based Automatic Control for Water Pumping Machine and Level Indicator (MBACWPMLI) has been designed, constructed and tested. The MBACWPML I uses the reflection of sound (echo) to give the indication of water level in a storage tank and also the automatic control of the water pumping machine. The MBACWPMLI uses ultrasonic sensor installed at the top of a tank to send and receive sound waves, and the time taken is converted to distance by the microcontroller to give corresponding digital outputs which turns ON LEDs that indicate the level of water in the storage tank. The microcontroller also gives digital output to turn ON the water pump (when the water in the tank is at a preset minimum level of 0.27 metres) or turn OFF the water pump (when the water goes above the chosen maximum level of 0.05 metres). The MBACWPMLI when tested turned ON or OFF the water pump at the preset minimum and maximum level and the required LEDs were also turned ON at the corresponding water level. http://dx.doi.org/10.4314/njt.v35i3.16